Consultation meeting with key stakeholders - Sawadogo, Seraphine; Balima, Mariam; Ouédraogo, Issa (CGIAR Challenge Program on Water and Food, 2011)
The  consultation  workshop  with  Burkinabe  key  stakeholders  for  the  V1  Project  within  the   Challenge  Program  on  Water  and  Food  (CPWF)  of  the  Volta  Basin  took  place  from  14  to  15   March  2011  in  Ouagadougou.  The  meeting  room  of  the  DIST  in  CNRST  was  booked  for  the   first  day  while  in  the  second  day,  the  workshop  took  place  in  the  conference  room  of  the   National  Archives  Centre.